INVERSE VULCANIZATION OF COPOLYMERS FOR SLOW-RELEASE UREA FERTILIZERS: SYNTHESIS, PERFORMANCE ANALYSIS AND REGRESSION MODELLING - MANZOOR GHUMMAN, ALI SHAAN (2021)
Inverse vulcanized copolymers made of high sulfur content and vegetable oils are green and sustainable polymers produced using a solvent free method. However, the copolymers produced using edible oils are expensive due to demand in the food market. Therefore, to overcome these limitations, utilization of non-edible oil as comonomer is highly recommended. The main objective of this study is to develop slow-release fertilizer using inverse vulcanized copolymers to enhance the utilization of sulfate by plant, improve the efficacy of nutrient uptake and reduce the environmental impact, with better sulfate release performance and good bio-degradation capability. In this study, rubber seed oil was used as a monomer to produce sulfur enriched copolymer and optimization of the reaction condition was carried out to minimize the amount of the unreacted sulfur using response surface methodology. The copolymer produced was then characterized using FTIR, TGA, DSC, SEM, and p-XRD. Two types of slowrelease fertilizers were then prepared: slow-release urea matrices by mixing in-situ the pre-polymer with powdered urea and slow-release coated urea by coating the urea granules with the copolymer. The copolymer produced under optimized conditions (164C reaction temperature, 50.57 wt% of sulfur and 73.67 mins reaction time) significantly increased the sulfur conversion to 94.2%. ANOVA showed a coefficient of correlation (R2) of 0.9690, F-value of 87.44, and p-value of <0.0001, which shows the goodness of the quadratic model developed. The nutrient release performance of the slow-release fertilizers was evaluated in distilled water. The slow-release matrices released >75% of its total nutrients in 21 days of incubation, whereas the coated urea released was only 37%. Ritger-Peppas law best fit the kinetic release data and explained that the best samples follow a non-Fickian diffusion mechanism. The copolymer produced under optimized conditions also demonstrated better sulfur oxidation than elemental sulfur as no sudden drop in sulfate release was found during submerged cultivation. The soil burial test revealed the bio-degradability of the copolymer with almost 38% weight loss in 90 days.